Examination of Muslim Zilennial Consumers’ Intentions to Eat at Popular Restaurants : Do Islamic Values Matter? - Mia Sari (Maqasid al-Shariah Review, 2022)
In the current onslaught of digitalization era, understanding the intentions and preferences of Zilennial consumers towards popular restaurants is crucial for researchers and business practitioners alike. Hence, this research aims to examine Muslim consumers' intentions to dine at "Restoeran Gacoan" using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The study involved 120 respondents to evaluate the impact of Symbolic Value, Hedonic Value, Islamic Value, and Functional Value on Muslim consumers' satisfaction at Restoeran Gacoan. The findings reveal that Symbolic Value, Hedonic Value, and Islamic Value significantly influence Muslim consumers' satisfaction at Restoeran Gacoan. However, Functional Value does not have a significant impact on their satisfaction. Additionally, the research also indicates that Muslim consumers' satisfaction has a positive effect on their willingness to pay more. This study provides valuable insights for restaurant managers, particularly at Restoeran Gacoan, to comprehend the factors influencing Muslim consumers' satisfaction and their willingness to pay more. This understanding can aid restaurants in designing more effective and responsive marketing strategies that cater to the needs and preferences of Muslim consumers.